Managing Online Buying and Selling Products for UUM Students - Mohammad Rababa, Othman Mahmoud (2012)
University Utara Malaysia (UUM) has more than 28 thousand local students and more than two thousand international students. After conducting interviews with some of UUM students, the researcher found that the majority of them have had a lot of difficulties during their staying in this region; one of those difficulties is to find primary products. Each student especially international students, need to buy basic needs during the early days in UUM within short time. On other side, they need to sell them again in certain time when they finish their studying. This project aims to develop a system for managing selling and buying products or belongings which could be used to assist students in UUM to advertise their products and in an appropriate and quick way. This research will evaluate the acceptance of the proposed system.